Two for the Price of One: A Model for Parallel and Incremental Computation - Burckhardt, Sebastian; Leijen, Daan; Yi, Jaeheon; Ball, Thomas; Ball, Thomas (Proceedings of the ACM International Conference on Object Oriented Programming Systems Languages and Applications (OOPSLA'11), 2011)
Parallel or incremental versions of an algorithm can significantly outperform their counterparts, but are often difficult to develop. Programming models that provide appropriate abstractions to decompose data and tasks can simplify parallelization. We show in this work that the same abstractions can enable both parallel and incremental execution. We present the first known algorithm for parallel self-adjusting computation. This algorithm extends a deterministic parallel programming model (concurrent revisions) with support for recording and repeating computations. On record, we construct a dynamic dependence graph of the parallel computation. On repeat, we reexecute only parts whose dependencies have changed. We implement and evaluate our idea by studying five example programs, including a realistic multi-pass CSS layout algorithm. We describe programming techniques that proved particularly useful to improve the performance of self-adjustment in practice. Our final results show significant speedups on all examples (up to 37x on an 8-core machine). These speedups are well beyond what can be achieved by parallelization alone, while requiring a comparable effort by the programmer. This paper won an OOPSLA Distinguished Paper Award.